1984
DOI: 10.1093/nar/12.12.4881
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequences of the 5 S rRNAs of seven moids and a yeast and their use in studying ascomycete phylogeny

Abstract: The sequences of the 5 S rRNAs isolated from 8 ascomycete species belonging to the genera Aspergillus, Penicillium, Acremonium and Candida are reported. Two of the examined strains each yielded a mixture of 3 slightly different 5 S RNAs, which were individually sequenced after fractionation. A previously published sequence for Aspergillus nidulans 5 S RNA was found to contain errors. Reconstruction of an evolutionary tree based on 5 S RNA sequences showed that the 16 presently examined ascomycetes form three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…thaliana minor 5S RNAs differ from the major 5S RNA by one or two base substitutions, as has been described for Escherichia coli (Jarry and Rosset, 1971), and we found many different 5S RNA, as reported in Neurospora (Chen et al 1984). However, only in Escherichia coli, Xenopus, and Neurospora (Selker et al 1985), has it been shown that heterogeneous 5S RNA exist in polysomes.…”
Section: Genome Research 139supporting
confidence: 87%
See 2 more Smart Citations
“…thaliana minor 5S RNAs differ from the major 5S RNA by one or two base substitutions, as has been described for Escherichia coli (Jarry and Rosset, 1971), and we found many different 5S RNA, as reported in Neurospora (Chen et al 1984). However, only in Escherichia coli, Xenopus, and Neurospora (Selker et al 1985), has it been shown that heterogeneous 5S RNA exist in polysomes.…”
Section: Genome Research 139supporting
confidence: 87%
“…In addition to the major 5S RNA species, minor RNA species represent 18% of total 5S RNA. Heterogeneity in 5S RNA has also been reported for a wide range of organisms including bacteria (Jarry and Rosset, 1971), fungi (Wildelman and Nazar, 1982;Chen et al 1984), echinoderms (Lu et al 1980), arthropods (Komiya et al 1980), amphibia (Ford and South- …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This pattern differed strikingly, in several instances, from that observed in a compilation of genes from the single-celled ascomycete S. cerevisiae (5); differences in codon preference were most evident in Glu, Gln, Cys, Pro, and Arg codons. We speculate that these differences may reflect evolutionary distance between the yeasts and the filamentous ascomycetes (13).…”
Section: Resultsmentioning
confidence: 96%
“…C. albicans has been placed in the group Fungi Imperfecti, the group of fungi that are not known to have arty mating phase. However, sequence analyses of small ribosomal subunit RNAs and 5S rRNA reveal that C. albicans belongs to the order Endomycetales, to which the family Saccharomycetaceae also belongs (7,18). Significant degrees of DNA sequence homology between a number of C. albicans genes and the corresponding S. cerevisiae genes have been reported (2,36,44).…”
Section: Discussionmentioning
confidence: 99%